Failure to Detect SARS-CoV-2 RNA in the Air During Active Labor in Mothers Who Recently Tested Positive - Schoen, Corina N.; Morgan, Elizabeth; Leftwich, Heidi K.; Rogers, Christine; Soorneedi, Anand; Suther, Cassandra; Moore, Matthew D. (Frontiers in Public Health, 2022)
The risk of potential SARS-CoV-2 transmission by infected mothers during labor and delivery has not been investigated in-depth. This work collected air samples close to (respiratory droplets) and more distant from (aerosol generation) unvaccinated patients who had previously tested positive for SARS-CoV-2 during labor within 5 days of a positive test. All but one of the patients wore masks during the delivery, and delivery was carried out in either birthing or negative pressure isolation rooms. Our work failed to detect SARS-CoV-2 RNA in any air samples for all of the six patients who gave birth vaginally, despite validation of the limit of detection of the samplers. In sum, this brief report provides initial evidence that the risk of airborne transmission of SARS-CoV-2 during labor may be mitigated by the use of masks and high ventilation rates common in many modern U.S. medical facilities; however more work is needed to fully evaluate the risk of SARS-CoV-2 transmission during labor and maternal pushing.